Incidence and clinical characteristics of acute rheumatic fever in Turkey: Results of a nationwide multicentre study. (6th July 2021) - Gürses, Dolunay; Koçak, Gülendam; Tutar, Ercan; Özbarlas, Nazan; ,
Abstract : Aim: To evaluate the incidence and clinical features of acute rheumatic fever (ARF) in Turkey, following the revised Jones criteria in 2015. Methods: This multicentre study was designed by the Acquired Heart Diseases Working Group of the Turkish Pediatric Cardiology and Pediatric Cardiac Surgery Association in 2016. The data during the first attack of 1103 ARF patients were collected from the paediatric cardiologists between 1 January 2016 and 31 December 2016. Results: Turkey National Institute of Statistics records of 2016 were used for the determination of ARF incidence with regard to various cities and regions separately. The estimated incidence rate of ARF was 8.84/100 000 in Turkey. The ARF incidence varied considerably among different regions. The highest incidence was found in the Eastern Anatolia Region as 14.4/100 000, and the lowest incidence was found in the Black Sea Region as 3.3/100 000 ( P  < 0.05). Clinical carditis was the most common finding. The incidence of clinical carditis, subclinical carditis, polyarthritis, aseptic monoarthritis, polyarthralgia and Sydenham's Chorea was 53.5%, 29.1%, 52.8%, 10.3%, 18.6% and 7.9%, respectively. The incidences of clinical carditis, subclinical carditis, polyarthritis and polyarthralgia were found to be significantly different among different regions ( P  < 0.05). Conclusion: The findings of this nationwide screening of ARF suggest that Turkey should be included in the moderate‐risk group.